Pengaruh Penggunaan Media Pembelajaran Scrapbook untuk Meningkatkan Hasil Belajar IPA Peserta Didik Kelas IV Sekolah Dasar - Neng Elsa Novianti Ruhiat (caXra: Jurnal Pendidikan Sekolah Dasar, 2022)
The results of observations of science learning in class show that there are still many students who seem to have difficulty reading and understanding what the teacher is saying. Likewise, teachers have not used media that can help students understand learning more easily. Thus, there is a need for innovative changes in learning that are able to help students learn science more easily and interestingly. This study aims to determine: 1) the effect of student learning outcomes in science lessons; and 2) The effect of student learning outcomes in learning using Scrapbook learning media. Experimental method with quantitative and quasi-experimental approach in the form of One Group Pretest-Posttest Design. The research was conducted in the fourth grade of SDN 3 Mekarbakti Garut. The results of the study are as follows: 1) There is an effect of student learning outcomes in science lessons 2) The effect of student learning outcomes after using Scrapbook learning media. The conclusion in this study is that there is a significant effect of learning outcomes on science subjects after using Scrapbook learning media